2019
DOI: 10.1021/acsanm.9b01429
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Substituted Isoreticular Metal–Organic Framework for Efficient and Rapid Removal of Phosphate

Abstract: Excessive phosphate can cause water eutrophication. Adsorption can remove excessive phosphate in water to alleviate eutrophication effectively. Herein, an isoreticular metal–organic framework (Fe-IRMOF-3-10) with bimetallic center and double ligand was successfully synthesized from a single metal center and single ligand isoreticular metal–organic framework (IRMOF-3) to remove phosphate in water effectively. In the four IRMOFs, Fe-IRMOF-3-10 shows higher adsorption capacity (177.0 mg g–1 at 25 °C) and faster a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…The adsorption isotherm can reflect the interaction between HP-Fe-CF 3 -B and FCPs and the surface characteristics of the HP-Fe-CF 3 -B. It is generally verified and evaluated by Langmuir (eq ) and Freundlich (eq ) models Among them, C e (mg/L) and q e (mg/g) represent the concentration and adsorption capacity when HP-Fe-CF 3 -B adsorbs FCPs at equilibrium, respectively, q m (mg/g) represents the maximum adsorption capacity for FCPs, b and K F represent Langmuir and Freundlich constants, respectively, and 1/ n represents heterogeneity.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The adsorption isotherm can reflect the interaction between HP-Fe-CF 3 -B and FCPs and the surface characteristics of the HP-Fe-CF 3 -B. It is generally verified and evaluated by Langmuir (eq ) and Freundlich (eq ) models Among them, C e (mg/L) and q e (mg/g) represent the concentration and adsorption capacity when HP-Fe-CF 3 -B adsorbs FCPs at equilibrium, respectively, q m (mg/g) represents the maximum adsorption capacity for FCPs, b and K F represent Langmuir and Freundlich constants, respectively, and 1/ n represents heterogeneity.…”
Section: Resultsmentioning
confidence: 97%
“…To better explore the adsorption mechanism, the adsorption thermodynamics of HP-Fe-CF 3 -B on the adsorption of FCPs has been studied (eqs ). Among them, Δ G (kJ/mol), Δ H (kJ/mol), and Δ S (J/(mol K)) respectively represent Gibbs free energy, enthalpy change, and entropy change, K is the thermodynamic equilibrium constant, R is the ideal gas constant which is 8.314 J/(mol K), and T (K) is the temperature in Kelvin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of CO 3 2À on phosphate adsorption is relatively large compared to other anions, which may be due to the decrease in adsorption capacity due to the alkaline nature of the solution caused by CO 3 2À . 53 It was found that the pH = 10.95 for the solution after the addition of CO 3…”
Section: àmentioning
confidence: 99%
“…Therefore, MOFs and their derivatives have been intensively employed in these fields. In addition to conventional gas capture and separation including CO 2 uptake, hydrogen gas attraction, ammonia capture, and efficient separation between CO 2 and methane, , MOFs have been developed to remove arsenic and phosphate species from water. MOF-based nanosheets also exhibited interesting gate-opening gas adsorption .…”
Section: Capture Sensing and Separationmentioning
confidence: 99%